ANALISIS HUKUM PERAN KARANG TARUNA TUNAS KARYA DALAM MEWUJUDKAN TANGGUNG JAWAB SOSIAL PEMUDA (Jurnal De Jure Muhammadiyah Cirebon, 2021)
This study aims to examine youth organizations as youth-based social organizations that have an important role in realizing youth social responsibility in Manis Kidul Village, Jalaksana Kuningan. A person is legally responsible for a certain act or that he bears legal responsibility, subject means that he is responsible for a sanction in the case of a contradictory act. The type of research used is qualitative research, this research was carried out in the village of Manis Kidul, Jalaksana District, Kuningan Regency. Sources of data used in the form of primary and secondary data. Data collection techniques with interviews, observation and documentation. The results show that the role of youth organizations in realizing youth social responsibility invites the community to be active in the involvement of work programs that run on the basis of work programs based on the Minister of Social Affairs Regulation No. 25 of 2019 so as to realize Youth Social Responsibility towards caring for the environment of their community.Keywords: Youth Organization; Tunas Karya, Social Responsibility.